OSU based M-OTN networking modes and field trial - Ruiquan JING; Leiyang SHEN; Zhiwei JIN; Jing ZHANG; Yuan YAO; Lei CHENG; Heng ZHOU (Dianxin kexue)
The innovative optical service unit (OSU) based on M-OTN technologies can provide high-quality private line services with low latency and flexible bandwidth, and improve the networking capability and efficiency of OTN for small granularity services.The application mode of M-OTN/OSU technologies in the OTN were discussed, including the value OSU brings, the comparison of Overlay vs.Underlay networking modes, multiplexing modes of OSU into ODUk and multi-service unified transport.The service capability and long-term operational reliability of OSU technology were fully verified through the field trial network, which provides a technical basis for the selection of OSU networking modes.